The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1986
DOI: 10.1007/bf00925095
|View full text |Cite
|
Sign up to set email alerts
|

The life cycle ofBrachylaima ruminae n. sp. (Trematoda: Brachylaimidae), a parasite of rodents

Abstract: The life cycle of Brachylaima ruminae n.sp. (Trematoda: Brachylaimidae), a duodenal parasite of rodents on the Mediterranean island of Formentera (Spain) is elucidated. The new species follows a terrestrial triheteroxenous life cycle. Eggs passed in the faeces of the definitive host must be ingested by a specific first intermediate host, the land snail Rumina decollata. Branched cercariogenous sporocysts develop in the digestive gland. Microcercous cercariae come out through the terminal birth pores of the bra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
22
1
1

Year Published

1992
1992
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(25 citation statements)
references
References 9 publications
1
22
1
1
Order By: Relevance
“…nov. from E. gainesi in Hokkaido. The new species was at first thought to be an immigrant species due to the recent anthropogenic introduction of host animals, because the parasite showed morphological similarities to already known species from rodents of the genus Rattus [9,36,37,38,39]. However, the population genetics analysis of the parasite mtDNA suggests that the new species is originally indigenous to Hokkaido.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…nov. from E. gainesi in Hokkaido. The new species was at first thought to be an immigrant species due to the recent anthropogenic introduction of host animals, because the parasite showed morphological similarities to already known species from rodents of the genus Rattus [9,36,37,38,39]. However, the population genetics analysis of the parasite mtDNA suggests that the new species is originally indigenous to Hokkaido.…”
Section: Discussionmentioning
confidence: 99%
“…However, the population genetics analysis of the parasite mtDNA suggests that the new species is originally indigenous to Hokkaido. Several reports [37,40,41] …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Mas-Coma & Montoliu (1986) indicated that such variation can occur among brachylaimids. In the present study, two species, each found in three host species, were not found to vary morphologically between the hosts.…”
Section: Taxonomic Approachmentioning
confidence: 99%
“…Some researchers have previously reported the presence of metacercariae of Brachylaima spp. in the kidney, pericardial sac, body cavity near the female genital pore, and pedal glands of land snails (Mas-Coma and Montoliu, 1986;Thiengo and Amato, 1995;Butcher and Grove, 2001;Barger and Hnida, 2008;Barger, 2011;Segade et al, 2011;Valente et al, 2016;Nakao et al, 2017). The occurrence of Brachylaima sp.…”
mentioning
confidence: 99%